2001
DOI: 10.1021/ma010122r
|View full text |Cite
|
Sign up to set email alerts
|

Stereoregular and Stereoirregular Alternating Ethylene−Norbornene Copolymers

Abstract: Ethylene−norbornene (E−N) copolymers were synthesized with the C 2 metallocene rac-Me2Si(2-Me-[e]-benzindenyl)2ZrCl2 (3) and with the constrained geometry Me2Si(Me4Cp)(NtBu)TiCl2 (4) in the presence of methylaluminoxane. The E−N copolymerizations were carried out using a variety of monomer feed compositions. Copolymers were fully characterized by 13C NMR spectroscopy, gel permeation chromatography, and differential scanning calorimetry. Copolymer microstructures were analyzed in detail, through a procedure whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 23 publications
3
102
0
Order By: Relevance
“…Many have reported on ethylene copolymerization with norbornene (NBE) using ordinary metallocenes [10][11][12][13][14][15][16][17], half-titanocenes [18][19][20][21][22][23][24][25][26], and others [27][28][29][30], however, successful examples of the efficient synthesis of random, high molecular weight copolymers with high Tg values (high NBE content) have been limited. Ethylene copolymers with tetracyclododecene (TCD, dimethanooctahydronaphthalene) are also known as promising materials [9], and are produced by using classical Ziegler-type vanadium catalyst systems (VOCl3, VO(OEt)Cl2-EtAlCl2•Et2AlCl, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Many have reported on ethylene copolymerization with norbornene (NBE) using ordinary metallocenes [10][11][12][13][14][15][16][17], half-titanocenes [18][19][20][21][22][23][24][25][26], and others [27][28][29][30], however, successful examples of the efficient synthesis of random, high molecular weight copolymers with high Tg values (high NBE content) have been limited. Ethylene copolymers with tetracyclododecene (TCD, dimethanooctahydronaphthalene) are also known as promising materials [9], and are produced by using classical Ziegler-type vanadium catalyst systems (VOCl3, VO(OEt)Cl2-EtAlCl2•Et2AlCl, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The structure of these copolymers has been extensively studied using 13 C high resolution in solution [5][6][7]. It was found that in copolymer with low NB content the close vicinity of two or more NB groups is rather rare.…”
Section: Introductionmentioning
confidence: 99%
“…The thorough microstructure investigation of E-co-N copolymers has taken several years [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. A number of groups dedicated great efforts to assign the 13 C NMR spectra of E-co-N copolymers.…”
Section: Methodologies For Signal Assignmentsmentioning
confidence: 99%
“…Utilizing the observed peak areas of the assigned 13 C signals and accounting for the stoichiometric requirements, it was possible to compute the molar fractions of the stereosequences, which define the microstructure of an alternating E-co-N copolymer containing meso (m) and racemic (r) alternating sequences [26].…”
Section: Methodsmentioning
confidence: 99%